If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = (x + 2) * 3 Reorder the terms: 4x = (2 + x) * 3 Reorder the terms for easier multiplication: 4x = 3(2 + x) 4x = (2 * 3 + x * 3) 4x = (6 + 3x) Solving 4x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4x + -3x = 6 + 3x + -3x Combine like terms: 4x + -3x = 1x 1x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 1x = 6 + 0 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 15-(-6)= | | -1+(-2)+(-8)+(-6)= | | 42+(x-5)+(2x-15)=180 | | 6g+5-2(g+2)=-(-7g-1) | | (6a-4a^2)+(8+9a)= | | 0.3x-7=x/2 | | 13+(-6)+(-10)+(-8)= | | 3x^3-5x^2+9x-15=0 | | -18+4+(-2)+12= | | 8-2(2x+4)=-20 | | 3-4(x-5)=x-(2x+7) | | 3y=9(x-1) | | -20+5+(-7)+9= | | 2x-31= | | 12x^2-36x^3=0 | | 5a-11a=-6 | | 5+m=m-3 | | X-5=Y | | 3(b-9)=-39 | | 2e^2+e-3=0 | | 3X^2-3X+1+X^2+3X-1=0 | | x^2+7x+y^2+1y=-16 | | 5+(-1)+(-12)+8= | | x^2+7x+y^2+1y-16=0 | | 3x=9(x-1) | | -5x-8=-7x+1 | | 8=8v-4(4+8) | | (8k+9)-(k+2)= | | 2+1.10x=5+.95x | | 3h^2+14h-5=0 | | 4w^2+8w+3=0 | | 284+-35y=4 |